2020
DOI: 10.1111/ajag.12859
|View full text |Cite
|
Sign up to set email alerts
|

Who is taking care of the Chinese functionally impaired older people? The characteristics of family caregivers from China Health and Retirement Longitudinal Study

Abstract: Population ageing in China has led to millions of functionally impaired older people requiring physical care. 1 Disability is defined as an umbrella term for impairments, activity limitations and participation restrictions by the International Classification of Functioning, Disability and Health (ICF). 2 China is well-known to have the largest number of partially and completely functionally impaired older people in the world. 1 It is suggested that from 2015 to 2020, the number of functionally impaired older p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…In addition, Zhao et al [ 50 ] investigated the caregivers as the study’s primary research target, explicitly focusing on informal care contexts and the implications on caregivers’ quality of life and social and material deprivation. Belonging to this group, the study by Zhou et al [ 51 ] is one of the few articles focusing on the relationship between the health status of caregivers and that of “care recipients”, e.g., spouses or older parents requiring care. This is important since informal caregivers often complain about their mental state (anxiety, depression, exhaustion, etc.).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, Zhao et al [ 50 ] investigated the caregivers as the study’s primary research target, explicitly focusing on informal care contexts and the implications on caregivers’ quality of life and social and material deprivation. Belonging to this group, the study by Zhou et al [ 51 ] is one of the few articles focusing on the relationship between the health status of caregivers and that of “care recipients”, e.g., spouses or older parents requiring care. This is important since informal caregivers often complain about their mental state (anxiety, depression, exhaustion, etc.).…”
Section: Resultsmentioning
confidence: 99%
“…20,21 Second, spousal caregivers were the least likely of the family caregiver types to acquire outside aid, 22 relying primarily on their children. 4 However, the traditional Chinese concept of raising children for old age and filial piety is weakening, 4,23 which is why some spousal caregivers reported that they cared for their disabled partners. On the other hand, some spousal caregivers did not want to bother their children, which fit with the stereotype of Chinese parents doing everything they can do for their children and never expecting anything in return.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 Over 80% of older adults prefer to live with their family members rather than in nursing institutions, especially those who are functionally impaired. 4 Therefore, the traditional family pension remains China's dominant old-age security model, 5 and disabled older adults heavily rely on their family members to provide informal care for them. In most situations, however, 55% of family caregivers are their spouses, 6 who share the primary responsibility of caring for their disabled partners 4 due to family size reductions and the younger generation being overloaded with work.…”
Section: Introductionmentioning
confidence: 99%
“…Caregiving tasks are carried out almost exclusively by family caregivers. 13 These family caregivers are not paid for their care services and have low levels of education and training. 14 However, family caregivers are progressively occupied with increasing demands and have less time to devote to their own needs, career planning and daily life.…”
Section: Introductionmentioning
confidence: 99%
“…Family caregivers play a significant role in long-term home care for disabled elderly people, and these are primarily children, spouses and other family members. Caregiving tasks are carried out almost exclusively by family caregivers 13. These family caregivers are not paid for their care services and have low levels of education and training 14.…”
Section: Introductionmentioning
confidence: 99%